2013
DOI: 10.1111/ped.12134
|View full text |Cite
|
Sign up to set email alerts
|

Acute alcohol intoxication in a 15‐day‐old neonate

Abstract: We describe a 15-day-old newborn girl who was fed with formula milk that was accidentally diluted with sake (Japanese wine prepared from fermented rice). The clinical features were flushed skin, tachycardia and low blood pressure indicating circulatory failure, somnolence and metabolic acidosis without hypoglycemia. The serum ethanol concentration was 43.0 mg/dL at 3 h after intake. The patient recovered under intravenous fluid replacement without complications. Follow-up examinations at 1, 2, 3, 6 and 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“… 7 , 16 Incidental alcohol concentrations in newborn infants that cause severe physical symptoms or death have been reported at BACs greater than or equal to 43 mg/dL. 17 , 18 However, these studies observed the toxic effects caused by a single or intermittent high-concentration alcohol exposure. Therefore, the risk of intoxication cannot be applied to cases of sustained low-concentration exposure found in infants in incubators.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 16 Incidental alcohol concentrations in newborn infants that cause severe physical symptoms or death have been reported at BACs greater than or equal to 43 mg/dL. 17 , 18 However, these studies observed the toxic effects caused by a single or intermittent high-concentration alcohol exposure. Therefore, the risk of intoxication cannot be applied to cases of sustained low-concentration exposure found in infants in incubators.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol intoxication is uncommon in children, especially neonates [ 7 ]. According to previous reports, the clinical symptoms of acute ethanol intoxication are non-specific, and can be confused with other diseases, such as encephalitis, hydrocephalus, and anaphylactic shock [ 7 , 8 ].Therefore, we reported a case of acute ethanol intoxication in a 25-day-old newborn boy to raise awareness of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unintentional mixing of alcohol in formula is another way for neonates to consume ethanol. In Japan, a case [ 8 ] was reported where sake (Japanese wine prepared from fermented rice) was mixed in a 15-day-old newborn girl’s formula. The clinical features of the girl were flushed skin, tachycardia and low blood pressure indicating circulatory failure, somnolence and metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, serum ethanol concentrations of 50 to 100 mg/dL can lead to acidosis, central nervous system disturbances, respiratory distress, hypoglycemia, and coma. Concentrations generally peak 30 to 60 minutes after exposure [ 6 ]. As our patient presented over eight hours after the predicted exposure, the peak ethanol concentration most likely was significantly higher than the 125 mg/dL found on the initial point of care glucose.…”
Section: Discussionmentioning
confidence: 99%